Broader expression of the mouse platelet factor 4‐cre transgene beyond the megakaryocyte lineage. (17th December 2014) - Pertuy, F.; Aguilar, A.; Strassel, C.; Eckly, A.; Freund, J.‐N.; Duluc, I.; Gachet, C.; Lanza, F.; Léon, C.
Summary Background Transgenic mice expressing cre recombinase under the control of the platelet factor 4 (Pf4) promoter, in the context of a 100‐kb bacterial artificial chromosome, have become a valuable tool with which to study genetic modifications in the platelet lineage. However, the specificity of cre expression has recently been questioned, and the time of its onset during megakaryopoiesis remains unknown. Objectives/Methods To characterize the expression of this transgene, we used double‐fluorescent cre reporter mice. Results In the bone marrow, Pf4‐cre‐mediated recombination had occurred in all CD42‐positive megakaryocytes as early as stage I of maturation, and in rare CD42‐negative cells. In circulating blood, all platelets had recombined, along with only a minor fraction of CD45‐positive cells. However, we found that all tissues contained recombined cells of monocyte/macrophage origin. When recombined, these cells might potentially modify the function of the tissues under particular conditions, especially inflammatory conditions, which further increase recombination in immune cells. Unexpectedly, a subset of epithelial cells from the distal colon showed signs of recombination resulting from endogenous Pf4‐cre expression. This is probably the basis of the unexplained colon tumors developed by Apcflox/flox;Pf4‐cre mice, generated in a separate study on the role of Apc in platelet formation. Conclusion Altogether, our results indicate early recombination with full penetrance in megakaryopoiesis, and confirm the value of Pf4‐cre mice for the genetic engineering of megakaryocytes and platelets. However, care must be taken when investigating the role of platelets in processes outside hemostasis, especially when immune cells might be involved.